A Prospective Study Evaluating IOP Changes after Switching from a Therapy with Prostaglandin Eye Drops Containing Preservatives to Nonpreserved Tafluprost in Glaucoma Patients. (19th April 2012) - Ranno, Stefano; Sacchi, Matteo; Brancato, Cinzia; Gilardi, Daniela; Lembo, Andrea; Nucci, Paolo
Abstract : Purpose . To compare the ocular hypotensive effect of tafluprost with prostaglandin analogues (PGAs) in glaucoma patients. Methods . 89 primary open-angle glaucoma patients treated with bimatoprost, latanoprost, or travoprost for at least 3 months complaining for ocular discomfort were switched to tafluprost. IOP was assessed at baseline and 3 months after switching the therapy by daily curve. Primary outcome was to compare the mean daily IOP of tafluprost with PGAs. Results . The mean daily IOP was 16 ± 2.1 and 16.6 ± 2.0 mm Hg at baseline and after switching to tafluprost, respectively (P > 0.05 ). When analysis was carried out between tafluprost and each previous PGAs, the comparison between latanoprost and tafluprost and travoprost and tafluprost did not show any statistically significant difference in mean daily IOP and at each time point. The comparison between bimatoprost and tafluprost showed a statistically significant difference in mean daily IOP (P < 0.05 ) and at each time point (P < 0.05 ). Conclusions . After 3 months of switching tafluprost showed an overall IOP lowering effect similar to others PGAs. When each PGA was compared with tafluprost, bimatoprost showed to provide a statistically significant additional IOP lowering effect.